2020
DOI: 10.1021/acsami.0c17957
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PDA-Mediated Magnetic Bimetallic Nanozyme and Its Application in Immunochromatographic Assay

Abstract: Immunochromatographic assay (ICA) is widely applied in various fields. However, severe matrix interference and weak signal output present major challenges in achieving accurate and ultrasensitive detection in ICA. Here, a polydopamine (PDA)-mediated magnetic bimetallic nanozyme (Fe 3 O 4 @PDA@Pd/Pt) with peroxidase-like activity was synthesized and used as a probe in ICA. The magnetic property of Fe 3 O 4 @PDA@Pd/Pt enabled effective magnetic enrichment of targets, thereby reducing the matrix interference in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…The ζ-potential indicated the stability of the nanodispersion. The absolute values of the ζ-potential in 0–10 mV, 10–20 mV, 20–30 mV, and above 30 mV were defined as extreme instability, relative stability, moderate stability, and high stability, respectively . Thus, the IrO 2 @PDA-10 was the most stable, which was selected as the signal label of ICA for the follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ζ-potential indicated the stability of the nanodispersion. The absolute values of the ζ-potential in 0–10 mV, 10–20 mV, 20–30 mV, and above 30 mV were defined as extreme instability, relative stability, moderate stability, and high stability, respectively . Thus, the IrO 2 @PDA-10 was the most stable, which was selected as the signal label of ICA for the follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1B showed that IrO 2 NPs, IrO 2 @PDA-5, IrO 2 @PDA-10, IrO 2 @PDA-15, and IrO 2 @PDA-20 had ζ-potentials of −5. 33 Thus, the IrO 2 @PDA-10 was the most stable, which was selected as the signal label of ICA for the follow-up experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of immunochromatographic signals with nanozymes has become a new research hotspot in recent years. [17][18][19][20][21][22] Various nanozyme materials exhibit excellent catalytic activities by imitating the structure or function of natural enzymes, including metal and metal oxide nanoparticles (NPs), carbon nanomaterials, and various metal-organic frameworks. 23 Compared with proteases, nanozymes are characterized by higher catalytic stability, simple modification, and lower manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has started to focus on developing POCT kits that are based on dual-mode on-site detection, which requires multiple noble nanoparticles or QDs. The metals such as Au-Ag, Au-Pt, Pt-Pd, and QDs have been used in RDT kits; however, so far improvements to the LOD have only been obtained using these methods with single-mode approaches [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Although our group has previously developed RDT devices for single-mode detection [ 22 ], several commercial EuNPs, such as florescent dyes [ 23 ], aliphatic amine latex beads [ 24 ], CdSe/CdS/ZnS QDs, and latex coated CdSe/CdS/ZnS QDs [ 17 ], show good sensitivity (93%) and specificity (100%).…”
Section: Introductionmentioning
confidence: 99%